2018
DOI: 10.1016/s0140-6736(18)31388-6
|View full text |Cite|
|
Sign up to set email alerts
|

Esomeprazole and aspirin in Barrett's oesophagus (AspECT): a randomised factorial trial

Abstract: SummaryBackgroundOesophageal adenocarcinoma is the sixth most common cause of cancer death worldwide and Barrett's oesophagus is the biggest risk factor. We aimed to evaluate the efficacy of high-dose esomeprazole proton-pump inhibitor (PPI) and aspirin for improving outcomes in patients with Barrett's oesophagus.MethodsThe Aspirin and Esomeprazole Chemoprevention in Barrett's metaplasia Trial had a 2 × 2 factorial design and was done at 84 centres in the UK and one in Canada. Patients with Barrett's oesophagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 30 publications
4
150
1
8
Order By: Relevance
“…Indeed, a recent publication from the Aspirin Esomeprazole Chemoprevention Trial (AsPECT) provides the best data to date. That study showed that high‐dose PPI, especially when taken with aspirin, reduces the risk of neoplastic progression and mortality in patients with Barrett's oesophagus …”
mentioning
confidence: 97%
“…Indeed, a recent publication from the Aspirin Esomeprazole Chemoprevention Trial (AsPECT) provides the best data to date. That study showed that high‐dose PPI, especially when taken with aspirin, reduces the risk of neoplastic progression and mortality in patients with Barrett's oesophagus …”
mentioning
confidence: 97%
“…A nested case-control study in more than 1,000 US Veterans confirmed this effect, which was even more obvious with higher doses of PPI (OR 0.11; 95% CI 0.04-0.36) [14]. Recently, the effect of PPI on the prevention of further progression of BO has been prospectively assessed in the AspECT trial [15]. A total of 2,557 patients were recruited in 84 UK centres and one in Canada before randomisation in a 2-by-2 factorial design to assess the long-term effect of Esomeprazole (20 vs. 40 mg) each with or without Aspirin (300 mg).…”
Section: Chemopreventionmentioning
confidence: 93%
“…The use of Aspirin was beneficial only when patients with the use of further NSAIDs at inclusion were censored. The combination of high dose PPI plus Aspirin showed the best outcome regarding chemoprevention of BO and the complications mentioned above as included in the composite primary endpoint [15]. The number needed to treat to prevent a primary event was 34 for PPI and 43 for Aspirin.…”
Section: Chemopreventionmentioning
confidence: 97%
“…The prevention effect on gastric cancer was more prominent in those who used aspirin daily or for 5 or more years. Furthermore, it has been reported that PPIs and aspirin combination therapy may prevent esophageal adenocarcinoma in Barrett's eosophagus . Concerning the relationship between aspirin and events of gastrointestinal bleeding, Garcia Rodriguez et al reported that concomitant use of PPIs and aspirin decreased upper gastrointestinal bleeding risks relative to aspirin monotherapy .…”
Section: Can H Pylori Treatment Reduce the Incidence Of Gastric Cancer?mentioning
confidence: 99%